CSR Actions in companies and perception of their reputation by managers: analysis in the rural area of an emerging country in the banking sector - Del Brio, Jesús Ángel (2018)
This paper tests, from a managerial point of view, the influence of Corporate Social Responsibility (CSR) actions directed towards health and environmental matters over the perception of a company’s reputation. The literature review suggests an absence of this kind of study focused on the banking sector of developing countries. CSR activities oriented to health and subsistence in the rural areas of emerging countries are proved to hold a positive influence on the perception of managers of the banking sector of corporate reputation. On the other hand, it has not been possible to validate whether CSR activities oriented to environmental issues (or infrastructure) in rural areas will positively influence the perception of Peruvian banking sector managers of corporate reputation. The outcomes mentioned seem plausible due to health and subsistence being undoubtedly the most valued factors among people living in rural areas, where there are the most development deficiencies. This work contributes by empirically analyzing a relationship barely addressed in the field of business administration: the influence of CSR and corporate reputation. Furthermore, the authors take the analysis to a context unexplored by previous researchers, applying the concepts to the banking sector of an emerging country.